A Method for Increasing the Capacity of Radio Systems of Short-Range Navigation - Шевцов, І. О.; Старокожев, С. В.; Сєріков, А. О.; Дацько, С. В.; Сухоруков, Д. О.; Мачоніс, Т. С.; Коротіч, О. В.; Чумак, В. С.; Білоцерківець, О. Г. (2022 IEEE 2nd Ukrainian Microwave Week (UkrMW), 2022)
In the presented work, based on the representation of the total flow of range request signals, as well as intentional correlated and uncorrelated interference to a range-finding radio beacon as a Poisson flow, the capacity of both the range-finding beacon range transponder and the short-range radio engineering system as a whole is estimated based on the implementation of the method for extracting synchronous sequences of incoming range interrogation signals in the ground range transponder. It allows on a succession basis to move from the service signal to a requester service and, as a result, increase the throughput of the long -range radio beacon in question.
Keywords: Global navigation satellite systems; distance measuring equipment; GNSS